2015
DOI: 10.1007/s11069-015-1694-x
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the progressive eutrophication behind the world’s largest macroalgal blooms with water quality and ocean color data

Abstract: World's largest macroalgal blooms (MAB) caused by Ulva prolifera outbreak every summer in the Yellow Sea since 2007, which bring potential damage to regional marine environment and economics. Assessing the evolution of historic eutrophication status is of importance for exploring the reasons for the blooms. In this study, we used an area-weighted nutrient pollution index (AWCPI-NP) and ocean color data to assess temporal changes in eutrophication status in the Yellow Sea basin. Results show that significant sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 27 publications
1
41
1
Order By: Relevance
“…Overall, maximum daily CoPA (Table 1) is significantly lower than reported in Hu et al (2010) because of the much higher upper bound used in pixel unmixing in this study, and also significantly lower than all previously reported coverage when all algaecontaining pixels were treated the same (e.g., Xing et al, 2015b; Table 1). Interestingly, the ratio of CoPA to coverage of algaecontaining pixels appears to be separated for low and higher coverage: 5-6% when CoPA is <160 km 2 but 10-11% when CoPA is >500 km 2 .…”
Section: Uncertainties In Ulva Coverage Estimatescontrasting
confidence: 70%
See 4 more Smart Citations
“…Overall, maximum daily CoPA (Table 1) is significantly lower than reported in Hu et al (2010) because of the much higher upper bound used in pixel unmixing in this study, and also significantly lower than all previously reported coverage when all algaecontaining pixels were treated the same (e.g., Xing et al, 2015b; Table 1). Interestingly, the ratio of CoPA to coverage of algaecontaining pixels appears to be separated for low and higher coverage: 5-6% when CoPA is <160 km 2 but 10-11% when CoPA is >500 km 2 .…”
Section: Uncertainties In Ulva Coverage Estimatescontrasting
confidence: 70%
“…After 2008, some moderate blooms (i.e., >10% but <50% in the maximum daily CoPA referenced against maximum daily CoPA in 2008, Table 1) were found between 2009 and 2012, after which the bloom area increased annually to reach a maximum in 2015. Indeed, in 2015, the annual mean CoPA reached 116 km 2 , representing the largest Ulva bloom in this region (Xing et al, 2015b;SOA, 2016) and almost 4 times of the annual bloom size in 2008. However, in coastal waters near Qingdao (red circles in Fig.…”
Section: Results: Ulva Distributions Areal Coverage and Temporal Chmentioning
confidence: 98%
See 3 more Smart Citations